PENGARUH MODEL THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1KECAMATAN KAPUR IX - Raula Syah Desra; Dina Ramadhanti; Febrina Riska Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low descriptive text writing skills of seventh grade students of SMP Negeri 1, Kapur IX District. Students have difficulty understanding the structure and linguistic rules of descriptive texts, coupled with the use of less varied learning models. One model that is considered capable of improving writing skills is Think Talk Write (TTW). This study aims to describe the effect of the TTW model on students' descriptive text writing skills. The type of research is a quantitative experiment with a one-group pretest-posttest design. The research population was all seventh grade students, with a sample of class VII.2. The research data were in the form of descriptive text writing scores before and after treatment. The results of the study showed: first, writing skills before using TTW obtained an average of 47.09 (almost sufficient qualification), students still had difficulty in the closing structure and the use of linguistic elements. Second, after the application of TTW, the average increased to 79.89 (good qualification), students were more systematic in writing and understanding text rules. Third, the TTW model proved to have a positive effect, because through the think stage students practiced critical thinking, the talk stage encouraged active discussion, and the write stage improved writing skills. Thus, the TTW model is effective in improving junior high school students' descriptive writing skills.